Anthropometric standardisation of multiarticular leg extension movements: A theoretical study - Hahn, D.; Schwirtz, A.; Huber, A. (Isokinetics and Exercise Science, 2005)
The purpose of this study is to offer standardisation of multi-articular leg extension movements for isokinetic testing, based on a two link rigid body model with equal length of thigh and shank. Such standardisation corrects interindividual variations and may enable the derivation of the force-length-velocity [F(l, v)] characteristics during multiple joint (MJ) activities.